Скальная архитектура христианского Херсонеса–Херсона (ІV–Х вв.) - Сорочан, С.Б. (My University, 2015)
THE ROCK-HEWN ARCHITECTURE OF THE CHRISTIAN CHERSONESUSCHERSON (4th–10th century) (Summary) Prof. Sergey Sorochan The report aims at presenting all known evidences for these sacral monuments of the Early Byzantine Chersonesus-Cherson, which can be referred to the sites of the rock-hewn architecture. A classification for them is proposed, distinguishing the shared features and the specifics, which allows the presumption for three varieties of these facilities: martyria with underground level, tomb or a crypt; rock-hewn burial tombs, some of which can be sites of the martyrium cult (mainly tombs with Christian frescoes); hagiasma and friaries, cut into the rock. To the civilian sites of this kind can be referred several large water-collection cisterns, partially cut into the rock at a significant depth, as much as this is allowed by the meters thickness of precipitation of the Sarmatian limestone on the site where the town is located. The earliest of these rock-hewn tombs are at the necropolis out of the town, inherited by the Christians from the pagan burials, hypogea of the first centuries AD. The construction of martyria with elements of rock-hewn architecture begins later and in its greater part is implemented mainly in the second half of the 6th – the early 7th century. This time is also referred to the implementation of the water-collection cisternt the large agora, which, in parallel to the martyria, has existed until the 10th-11th century. СКАЛНАТА АРХИТЕКТУРА НА ХРИСТИЯНСКИЯ ХЕРСОНЕС-ХЕРСОН (ІV–Х вв.) (Резюме) Проф. Сергей Сорочан В доклада е направен опит да се представят всички известни сведения за тези сакрални паметници на ранно византийския Херсонес-Херсон, които могат да бъдат отнесени към обектите на скалната архитектура. Предложена е тяхна класификация, откроени са общи черти и особености, което позволява да се говори за три разновидности на тези съоръжения: мартирии с подземно ниво, гробница или крипта; скални погребални гробници, някои от които също могат да бъдат обекти на мартириалния култ (преди всичко гробници с християнски стенописи); изсечени в скалата агиасми и фреари. Към гражданските обекти от този род могат да бъдат отнесени някои големи водосборни цистерни, отчасти изсечени в скалата на значителна дълбочина, доколкото това позволява многометровата дебелина на отлаганията от сарматски варовик на мястото, където е разположен градът. Най-ранни от тях са скалните гробници на извънградския некропол, наследени от християните от езическите погребения, ипогеи от първите векове на н. е. Строителството на мартирии с елементи на скална архитектура започва по-късно и в голямата си част се осъществява предимно през втората половина на VІ – началото на VІІ вв. Към това време се отнася и устройството на водосборната цистерна на голямата агора, която, както и мартириите, е просъществувала до Х–ХІ вв.
Keywords: Херсонес; Херсон; христианство; скальная архитектура